Primary hyperparathyroidism with hungry bone syndrome - a case report - Jaafar, Khairul Azhar; Kamaruddin, Norazmi (Faculty of Medicine, International Islamic University Malaysia, 2007)
Primary hyperparathyroidism with severe bone disease as a result of excessive parathyroid hormone ( PTH ) release and severe hypercalcaemia can lead to 'hungry bone syndrome' (HBS) post operatively. This is due to sudden cessation of PTH and drop in serum calcium. We reported a case a young man with primary hyperparathyriodism due to a single parathyroid adenoma with severe bone disease and post operatively developed hungry bone syndrome.